SUICÍDIO INDÍGENA, PRÁTICAS DISCURSIVAS E(M) DOCUMENTÁRIO: por uma arqueogeneologia de O(s) Mistério(s) de Nhemyrõ - MONALISA IRIS QUINTANA (2023)
In 2020, according to data from the Socioenvironmental Institute (ISA), the outbreak of the COVID-19 pandemic brought new forms of suffering to the general population, as well, and, more specifically, to over 160 indigenous peoples. Simultaneously, it exposed the multiple violences exacerbating psychosocial distress within these communities. A probable consequence of this ongoing suffering is evidenced by the fact that the state of Mato Grosso do Sul (MS) historically records the second highest rate of indigenous suicides in Brazil. Guided by the theoretical-methodological assumptions of French Discourse Analysis and utilizing Foucauldian archeogenealogy (GREGOLIN, 2004; ARAÚJO, 2008; NAVARRO, 2020), this work aims to problematize the meanings surrounding the practice of suicide among the Guarani-Kaiowá indigenous peoples of MS (MORAIS, 2015; PIMENTEL, 2006) in the documentary series "O Mistério de Nhemyrõ" (The Mystery of Nhemyrõ). To fulfill this primary purpose, specific goals are formulated as follows: a) discussing how the technologies of biopower and biopolitics are related to the existential conditions of native communities and manifest the historical and discursive event of self-extinction (FOUCAULT, 1999; FOUCAULT, 2011) in the documentary; b) analyzing why the meanings of life and death, interwoven with indigenous memories and oral narratives presented in the documentary, come into conflict and can constitute a strategy of resistance in opposition to the hegemonic discourse. By an archeogenealogical perspective, I assume that by examining the ways and reasons certain mechanisms of power have solidified and established themselves as practices of knowledge concerning the bodies of subjects (NAVARRO, 2015), it becomes possible to establish a historical understanding for interpreting the present. To achieve this, regular statements (FOUCAULT, 2019) have been organized into enunciative sequences that, when described and interpreted, take into account the lived conditions of the period. My argued thesis is that, beyond clinical ways of conceptualizing such practices, discourses about suicide construct subjectivities, influencing indigenous representations of themselves, of others, and of us. Within the discursive framework of the documentary, the emergence of an indigenous intellectual representation functions as a narrative strategy that mobilizes native knowledge in both producing interpretations of suicide as a form of resistance, and subverting normalizing conceptions of self-inflicted death. Keywords: Discursive Practices. Indigenous Peoples. Suicide. Biopower.